Anjo de vanguarda: o catolicismo de Paulo Leminski - Simões, Eduardo Vagner Santos (Universidade Federal de São Carlos, 2024)
The thesis explores the Catholic thought in the works of Paulo Leminski, employing Edward Said's concept of Traveling Theory to argue for the transposition of Catholicism from its religious context to Leminski's intellectual production. Leminski's Catholicism is portrayed as a transmuted version, often an inverted Catholicism. Divided into four chapters, the research delves into different aspects of the author: biographer, novelist, essayist, and poet. In the first chapter, Leminski is examined as a biographer through the analysis of "Jesus a.C." (1984). Serving as a hermeneutic base for Leminski's Catholicism, this chapter explores the context of writing the biography during the strengthening of progressive Catholicism and counterculture. It discusses Leminski's portrayal of Jesus as a prophet and poet who challenges the major institutions of his time, offering utopian alternatives through his parables. The second chapter focuses on Leminski as a novelist, exploring "Agora é que são elas" (1984). The work, marked by a neobaroque aesthetic of profusion and polyphony, reflects on culture and the agonistic interplay between interdictions and transgressions. It thematizes true rites of return, in opposition to the merely operative rites of civilization, ultimately tensioning the realms of the sacred and the profane, as well as the concepts of providence and free will. The third chapter concentrates on Leminski's essayistic facet, analyzing essays such as "Alegria da senzala, tristeza das missões," where he draws parallels between enslaved Africans and Amerindians facing the symbolic violence of the colonizer; "Sem sexo, neca de criação," where he defends the idea of the "immigrant mystique of work," akin to Weber's concept of the "spirit of capitalism"; "Comunicando o incomunicável," discussing prayer in different religions; and "Corpo não mente," drawing parallels between Zen and Christianity. His essays reveal his ideas on spirituality and other religions. The fourth and final chapter explores Leminski as a poet, with emphasis on the posthumously published work "La vie en close" (1991). The research distinguishes between the poetry published from the early to mid-1980s and the posthumously published poems. It argues that "La vie en close" serves as a "testamentary work," where Leminski, employing a neobaroque aesthetic, thematizes and ritualizes his own death, including reminiscences of the monastery, facing the end with a certain eroticism. The research concludes that Leminski's Catholicism manifests in the belief in the demiurgic power of words to create utopias, questioning established values and subjecting them to life's scrutiny. It also presents a spirituality where daily acts, when internalized, awaken consciousness to the essence of life in all its violence and contradictions. This Leminskian Catholic expression proposes a new awareness capable of confronting life's violence in an erotic manner, celebrating it even in the face of death.
Anjo de vanguarda: Paulo Leminski's catholicism
Keywords: Leminski; Catolicismo; Barroco; Erotismo; Catholicism; Baroque; Eroticism; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA